Nutritional status of post-acute stroke patients during rehabilitation phase in hospital - Chong, Chin Weun; Nazirah Hasnan,; Lydia Abdul Latif,; Hazreen Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Malnutrition is highly prevalent among stroke patients during post-acute rehabilitation phase and may give a negative effect on rehabilitation and impair recovery. However, to date, there is no reported study in Malaysia investigating the nutritional status of stroke patients during rehabilitation phase. Thus, this paper aims to report the preliminary results of nutritional assessment for a randomized controlled trial at baseline. All participating patients were assessed for anthropometric measurements, nutritional status using validated Mini Nutrition Assessment (MNA), 24 h diet recall, and handgrip strength. Demographic data, biochemical profiles and functional outcomes (Modified Barthel Index Score, Motor Assessment Scale) were obtained from patients’ medical record. From a total of 45 post-acute stroke patients at baseline, 24.4% of them were malnourished during admission to rehabilitation ward and 66.7% of the patients were at risk of malnutrition. Mean dietary intake and protein intake of the patients were 1489 ± 297 kcal/day and 66.1 ± 17.2 g/day, respectively. Mean handgrip strength for the patients was 17.9 ± 8.1 kg. Weight, body mass index, serum albumin, handgrip strength, Modified Barthel Index and Motor Assessment Scale score were positively correlated with MNA score (p<0.05), but no correlation was found for the dietary intake (r=0.163, p=0.285) and protein intake (r=0.288, p=0.055). This preliminary result showed that stroke patients are particularly at risk of malnutrition or malnourished during the rehabilitation period. Therefore, early identification of malnutrition for stroke patients is important for a successful rehabilitation program.